2020
DOI: 10.1101/2020.04.15.20066688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in Aerosol Production Across Oxygen Delivery Devices in Spontaneously Breathing Human Subjects

Abstract: We sought to assess whether HHFNC results in greater production of aerosolized particles than 6 liters per minute nasal cannula, using state-of-the-art techniques of aerosol measurement, in spontaneously breathing human volunteers in a simulated hospital room. For each volunteer, we first measured background aerosol levels in the room immediately prior to testing. We then measured aerosol levels while the healthy volunteer laid in bed - - with the head of bed at 30 degrees - - wearing the following oxygen del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 13 publications
1
39
0
2
Order By: Relevance
“…We identified 3,523 unique citations using our electronic searches, 26 pre-prints from medRxiv, and one additional citation suggested by an expert panelist. We completed full-text review of 33 potentially eligible studies and included six studies, [53][54][55][56][57][58] and identified one additional study through reference list screening, 59 for a total of seven eligible studies (Fig. 9).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 3,523 unique citations using our electronic searches, 26 pre-prints from medRxiv, and one additional citation suggested by an expert panelist. We completed full-text review of 33 potentially eligible studies and included six studies, [53][54][55][56][57][58] and identified one additional study through reference list screening, 59 for a total of seven eligible studies (Fig. 9).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…9). [53][54][55][56][57][58][59] Of the seven eligible studies, six were simulation studies [53][54][55][57][58][59] and one was a crossover study. 56 No studies directly evaluated risk of aerosol generation or infection transmission associated with HFNC use among patients with COVID-19.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…With infectious pathogens with droplet or airborne spread, concern exists about potential exposure risk associated with using HFNC. However, newer evidence should alleviate this worry (33,34) and, as such, institutions who initially disallowed use of HFNC for COVID-19associated respiratory failure have begun to permit it. (35) In the context of a pandemic such as COVID-19, our priorities must shift slightly.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that the use of HFNC and NIV in patients with COVID-19 should be discouraged because of the risk of aerosol generation and exposure of health care workers [15][16]. Although no studies have directly evaluated the risk of aerosol generation or infection transmission associated with HFNC and NIV use in patients with COVID-19 [17][18][19][20][21][22][23][24], the use of NPPV and HFNC aggravates this risk through continuous open circuit viral aerosolization. If the patient is not in a negative pressure room, viral shedding through aerosol generation can extend beyond the room, thereby contaminating the hallways and beyond.…”
Section: Introductionmentioning
confidence: 99%